COVID-19’s effects on microvascular structure in a healthy retina: an OCTA study - Kazim Kiratli; Hazan Gul Kahraman; Yusuf Ziya Guven; Fahrettin Akay; Murat Aysin (International Journal of Ophthalmology)
AIM: To examine the subclinical alterations in the retina and choroid between patients with 2019 coronavirus disease (COVID-19)-related lung involvement and the healthy control group. METHODS: In this prospective case-control study, 85 cases with lung involvement due to COVID-19 and 50 healthy cases were included. Best-corrected visual acuity, intraocular pressure measurement, and anterior and posterior segment examination were performed on both eyes for each individual. Choroidal and retinal changes were examined and recorded by optical coherence tomography angiography. RESULTS: All choroidal thickness measurements of the COVID-19 group showed no statistically significant difference when compared to healthy individuals. When vascular density and perfusion density values were compared, there was a decrease in the average of these values in the COVID-19 group, although it was not statistically significant (P=0.088, P=0.065 respectively). When the fovea avascular zone (FAZ) area values were compared, the average was 0.57±0.38 in the COVID-19 group, while it was 0.54±0.24 in the control group. CONCLUSION: Although our data are not statistically significant, the decrease in vascularity and perfusion and the accompanying FAZ expansion are detected in the acute period (1st month). These changes may anatomically alter the retina in the long term and affect functional vision. Future ischemia-related alterations in the retina caused by a prior COVID-19 infection may arise in situations without comorbidities and may require concern in the patient's systemic assessment.